Rice seed production and distribution strategies in Palakkad district - Jinesh Jills George (Department of Agricultural Extension, College of Horticulture, 2002)
The present study on Palakkad rice seed system was basically aimed at understanding farmer-preferred varieties and attributes, the constraints to rice seed production and distribution at sub system level, public sector rice seed production status of the district for five consecutive years (1996-'97 to 2000-'01) and streamline a seed system strategy for Palakkad district. PRAIPLA investigations were conducted in ten ADBs (except Mannarkad and Agali) with 330 farmers (FSS), 41 AOs/AAs (ESS), 20 farm officials from the SSFs (SISS) and the rice researchers (RSS) of central zone as the respondents of the study. The analyses of data elicited through matrix ranking exercises was done using special 'preferential indices' developed namely MRI, VRI, ARI, CRI, MSAI. The results of the study confirmed the existence of a large number of rice varieties/cultivars (54 nos) raised in diverse agro climatic and micro-farming situations. Three unique systems apart from the traditional virippu and mundakan, namely Koottumundakan, Karingora and Poonthalpadams were identified. The major crop establishment system for virippu and mundakan were dry sowing and transplantation respectively. There was a huge gap in the demand and supply of quality rice seed facilitated by the SSFs, RARS, Pattambi, NSC unit, Alathur and RSGP. Together they accounted only for around five per cent of the rice seed requirement of the district. According to the latest estimates (2000-2001), 94.70 per cent of the rice seeds were farmer-produced, 1.51 per cent was contributed by SSFs, 0.66 per cent by RARS, Pattambi, 1.98 per cent by the NSC unit, Alathur and 1.15 per cent by RSGP. The 34 farmer-preferred rice varietal attributes were classified into eight categories namely, traits related to grain quality, multiple adaptability, pest/disease tolerance, straw quality, traits related to harvest and post harvest operations and traits related to inputs. The constraints to rice seed production and distribution at the various stakeholder systems (FSS, ESS, SISS and RSS) were classified into eight